PENGARUH CONTENT MARKETING DAN SOCIAL MEDIA ENGAGEMENT TERHADAP KEPUTUSAN PEMBELIAN MELALUI BRAND IMAGE SEBAGAI VARIBEL MEDIASI PADA MOMOYO TIKTOK SHOP DI KOTA PALANGKA RAYA - Simbolon, Petra; Tri Harinie, Luluk; Sukmani, Meylinda; Sintani, Lelo (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to examine the effect of content marketing and social media engagement on purchase decisions, with brand image as an intervening variable among Momoyo consumers on TikTok Shop in Palangka Raya City. The research employs a quantitative approach with an associative research design. Data were collected through an online questionnaire distributed to 100 respondents who had previously purchased Momoyo products via TikTok Shop. The collected data were analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS version 3.0 software. The results indicate that content marketing and social media engagement have a significant effect on purchase decisions. In addition, both variables also show a significant influence on brand image. Brand image is proven to mediate the relationship between content marketing and purchase decisions as well as between social media engagement and purchase decisions. These findings suggest that relevant content presentation and high levels of consumer engagement on social media can help build a positive brand image and encourage purchasing decisions. This study is expected to provide practical insights for businesses in developing more effective digital marketing strategies through the TikTok Shop platform.